Google Sites sebagai Media Pembelajaran Biologi: Kajian Literatur dan Implikasinya terhadap Proses Pembelajaran - Adi Firdarahman Sanjaya (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2025)
Google Sites has emerged as an alternative digital medium that can be utilized in biology learning, particularly in situations where teachers often overlook the use of instructional media due to limited facilities and lack of training. Therefore, educators are encouraged to explore and identify appropriate learning media to support effective teaching and learning processes. This study aimed to describe the extent to which Google Sites has been utilized in biology learning and to evaluate the feasibility of this medium within the context of biology education. The research employed a literature review methodology, which included the formulation of research questions and objectives, systematic literature searching, inclusion screening, quality assessment of primary studies, data extraction, and data analysis and synthesis. The findings indicate that the use of Google Sites as a learning medium is widespread and has been extensively developed in biology education. Overall, the reviewed studies report high feasibility and practicality scores, suggesting that Google Sites is a highly suitable and practical medium for biology learning. Therefore, it can be concluded that Google Sites is feasible to be implemented as an instructional medium in biology education.